Differential impacts of digital interactive media and print media on mental health: mediating mechanism of health literacy and group heterogeneity - Yuan, Junfeng; Luo, Lin (Frontiers in Public Health, 2025)
BackgroundIn the digital era, media have become critical conduits for information dissemination, exerting increasing influence on mental health. Traditional print media and digital interactive media differ significantly in how individuals access and process information, potentially influencing psychological well-being through distinct mechanisms. Health literacy—the integrated capacity to acquire, understand, and apply health information—has been recognized as a key mediator in the relationship between media use and mental health. However, the precise mechanisms and age-related variations of this mediating effect remain underexplored.ObjectiveThis study aims to investigate the differential pathways through which print media and digital interactive media influence depressive symptoms (measured by the Patient Health Questionnaire, PHQ) and anxiety symptoms (measured by the Generalized Anxiety Disorder scale, GAD), with a focus on the mediating role of health literacy and its heterogeneity across age groups.MethodsUsing data from the 2021 China Mental and Behavioral Survey, a total of 9,966 adults aged 19 and older were selected as the study sample. Key variables included: independent variables—frequency of print media and digital interactive media use; mediating variables—three dimensions of health literacy (healthcare, disease prevention, and health promotion); and dependent variables—scores on depression and anxiety symptoms. Descriptive statistics, Spearman correlation analysis, ANOVA, and bootstrap-based mediation tests (resampled 1,000 times) were conducted to systematically examine how different media types affect mental health through specific mechanisms.ResultsDigital interactive media use was significantly positively correlated with all dimensions of health literacy (r = 0.242–0.297, p < 0.01). It directly reduced levels of depression and anxiety (PHQ-9 effect size = −0.138; GAD-7 effect size = −0.145) and partially mediated this effect through the “disease prevention” dimension of health literacy (β = −0.021, 95% CI [−0.105, −0.025]). In contrast, print media use was positively associated with depression and anxiety scores (r = 0.025–0.039, p < 0.05), and all three dimensions of health literacy—"healthcare,” “disease prevention,” and “health promotion”—exerted a suppressing effect on this relationship (β = 0.003–0.004). Moreover, these mechanisms varied significantly across age groups: among individuals aged 19–40 and 41–60, the “disease prevention” dimension served as the primary mediator; whereas in the 61 + age group, the “health promotion” dimension emerged as the dominant pathway.ConclusionPrint and digital interactive media influence mental health through different mechanisms, which vary significantly across age groups. Based on these findings, a stratified intervention strategy—"digital prevention + print promotion”—is recommended: for younger populations, leveraging digital media to enhance disease prevention awareness is essential, while for older populations, an integrated media ecosystem should be developed to reduce cognitive load. This study proposes a media-type-centered framework for mental health intervention, and future research should employ longitudinal designs to establish causal inferences.